Enamel matrix proteins in the treatment of periodontal sites with horizontal type of bone loss - (:unkn) unknown (WILEY, 2003)
Objectives: The present study aims to assess the clinical and radiographic outcome of horizontal type of bone loss over a period of 8 months following periodontal surgery with adjunctive use of enamel matrix proteins (EMP). Materials and Methods: Twenty patients, who received nonsurgical periodontal therapy and had radiographic horizontal bone loss with an associated probing depth (PD) of greater than or equal to4 mm at the maxillary incisor/canine segment, were included. One side of the selected segment divided by the mid-sagittal plane was treated with EMP as part of a crevicular flap. The other side was treated either with a similar intracrevicular (ICI) or a reverse bevel incision (RBI) as part of a conventional flap debridement. Therefore, patients were divided into two groups of 10 patients according to the type of incision performed on the control side. The analysis was based on a classification of two severity groups according to preoperative PD, with the patient's means of measurements for each treatment being the experimental units for the statistical analysis. Results: For pockets of 4-6 mm, EMP treatment was significantly better than the ICI/flap debridement in terms of PD reduction (p<0.001), relative attachment level (RAL) gain (p<0.001) and recession (REC) (p<0.05). Although sites exposed to EMP treatment exhibited significantly greater RAL gain than RBI/flap debridement sites (p<0.01), both treatments resulted in equally effective PD reduction. Less REC occurred with EMP application than with ICI-RBI/flap debridement (p<0.05). Treatment of shallow sites by the conventional flap with both incisions resulted in a tendency for loss of attachment whereas EMP treatment maintained the attachment levels. No significant difference in the degree of probing and radiographic bone levels was found between the treatments. Conclusion: EMP treatment showed better clinical improvements as compared to the conventional flap debridement performed with two different incisions. Clinical improvements were more pronounced at periodontal sites with deep, rather than shallow, periodontal pockets. The results of this study provided an important preliminary base for further clinical and histologic studies.
Keywords: enamel matrix proteins; horizontal bone loss; periodontal regeneration; clinical trial; GUIDED TISSUE REGENERATION; DERIVATIVE EMDOGAIN; INTRABONY DEFECTS; SPLIT-MOUTH; HISTOMETRIC EVALUATION; HISTOLOGIC EVALUATION; INFRABONY DEFECTS; MEMBRANES; SURGERY; ATTACHMENT